2019
DOI: 10.3389/fendo.2019.00823
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Stimulates Endothelial Progenitor Cells to Induce Endothelialization in Aneurysm Necks Through the SDF-1/CXCR4/NRF2 Signaling Pathway

Abstract: Aneurysm (AN) embolization is an important treatment for cerebral aneurysms. The endothelialization of the aneurysm neck is crucial for preventing aneurysm recurrence. Sitagliptin is a therapeutic drug for diabetes that has been reported to have cardiovascular-protective effects. This study investigated the effect of sitagliptin on endothelial progenitor cell (EPC) function and endothelialization of aneurysm necks after embolization. The effect of sitagliptin on aneurysm neck endothelialization was examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…SDF-1 is a chemokine that has a strong chemotactic effect on EPCs. After vascular injury, SDF-1 induces migration of EPCs to the injured area and promotes endothelialization [20,21]. Under hyperglycemic conditions miR-133a was found to be up-regulated and induced endothelial dysfunction through inhibition of eNOS [22].…”
Section: Discussionmentioning
confidence: 97%
“…SDF-1 is a chemokine that has a strong chemotactic effect on EPCs. After vascular injury, SDF-1 induces migration of EPCs to the injured area and promotes endothelialization [20,21]. Under hyperglycemic conditions miR-133a was found to be up-regulated and induced endothelial dysfunction through inhibition of eNOS [22].…”
Section: Discussionmentioning
confidence: 97%
“…SDF-1 is a chemokine that has a strong chemotactic effect on EPCs. After vascular injury, SDF-1 induces migration of EPCs to the injured area and promotes endothelialization 32 , 33 . Under hyperglycemic conditions, miR-133a was found to be up-regulated, and induced endothelial dysfunction through inhibition of eNOS 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al confirmed that metallothionein (MT) promotes the angiogenesis of EPCs mediated by the HIF-1 α /SDF-1/VEGF pathway [ 54 ]. Several studies proved that the SDF-1/VEGF pathway is vital to the angiogenesis of EPCs [ 55 , 56 ]. In our research, the expressions of the angiogenesis-related genes CD34, VEGF, MMP9, and SDF-1 were examined and found to be upregulated at an appropriate concentration of GO.…”
Section: Discussionmentioning
confidence: 99%